2013
DOI: 10.1021/jz400333k
|View full text |Cite
|
Sign up to set email alerts
|

Acceptor-Enhanced Local Order in Conjugated Polymer Films

Abstract: Disorder in conjugated polymers is a general drawback that limits their use in organic electronics. We show that an archetypical conjugated polymer, MEH-PPV, enhances its local structural and electronic order upon addition of an electronic acceptor, trinitrofluorenone (TNF). First, acceptor addition in MEH-PPV results in a highly structured XRD pattern characteristic for semicrystalline conjugated polymers. Second, the surface roughness of the MEH-PPV films increases upon small acceptor addition, implying form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…6) becomes irrelevant and therefore the recombination rates approach the exponential behavior (Figure 7b). Most probably, the previously observed self-organization of the polymer chains in crystalline domains due to the CTC formation 14 adds another dimension to this scenario; a more detailed investigation on this issue is underway. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Visible-IR PIA spectroscopy has been further employed to study excited-state charge separation and recombination dynamics.…”
Section: Photoinduced Charge Generation and Recombinationmentioning
confidence: 92%
“…6) becomes irrelevant and therefore the recombination rates approach the exponential behavior (Figure 7b). Most probably, the previously observed self-organization of the polymer chains in crystalline domains due to the CTC formation 14 adds another dimension to this scenario; a more detailed investigation on this issue is underway. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Visible-IR PIA spectroscopy has been further employed to study excited-state charge separation and recombination dynamics.…”
Section: Photoinduced Charge Generation and Recombinationmentioning
confidence: 92%
“…Previous studies have indicated that dopant intercalation between polymer π-π stacking planes can account for similar q xy oriented refl ections in doped PBTTT and MEH-PPV. [ 16,40 ] The short d -spacing of these q xy oriented (010) peaks may be attributed to the small size of the dopants and the strong coulombic attraction between the polymer and dopant ions. Moreover, it is not clear what fraction of each of the polymers forms the phase responsible for the in-plane (010) refl ections.…”
Section: Molecular Packingmentioning
confidence: 99%
“…Because CTC formation results in polymer chain planarization (see above), these domains can include ordered (aligned) polymer chains. In fact, domains of ordered polymer chains were observed in MEH‐PPV : TNF films,61 which are discussed in Section 4.2.…”
Section: Ground Statementioning
confidence: 98%
“…Recent X‐ray diffraction studies on MEH‐PPV : TNF blend films revealed that CTC formation could increase the film structural and electronic order 61. Figure 15 presents grazing‐incidence X‐ray diffraction (GIXD) data for pristine MEH‐PPV and 1 : 0.3 and 1 : 1 MEH‐PPV : TNF blend films 61. One can see that the neat MEH‐PPV film shows no clear diffraction features, but a uniformly decreasing scattering signal that reflects the amorphous film structure.…”
Section: Ground Statementioning
confidence: 99%